How psychosocial safety climate indirectly affects the psychological health of working couples? - Muhamad Nasharudin, Nurfazreen Aina (Korean Society of Occupational & Environmental Medicine, 2023)
Background: The study aimed to investigate the effect of psychosocial safety climate (PSC) on job demands, work-family conflict (WFC), family-work conflict (FWC), and psychological health. First, the study proposed that PSC moderates the association between job demands and WFC for both husband and wife. Second, the study predicted FWC mediates the relationship between WFC and depression through the “crossover” process.